Building an international arbitration hub: China’s competitiveness and direction - Chu, Beiping; Wang, Wei (Frontiers in Marine Science, 2022)
Chinese Government has deployed a key task to develop a modern shipping service industry (including maritime arbitration), and further set the goal of “exploring the establishment of a national arbitration legal service alliance for pilot free trade zones and an exchange and cooperation mechanism for Asia-Pacific arbitration institutions, so as to accelerating the formation of a global-oriented Asia-Pacific arbitration hub in China”. For this purpose, China has initiated the revision of the Arbitration Law of the People’s Republic of China, and foreign-related arbitration institutions in China have invested considerable resources in exploring ways to improve their level of arbitration services. The Chinese arbitration community has also been exploring the possibility of establishing an international arbitration hub in China. This paper discusses whether China has the competitive advantages to establish an international arbitration hub and its possible direction of efforts from the perspective of comparative analysis of several major countries, regions or institutions that are currently in the leading position in the global arbitration service industry.